(NlITERATURA (BXIX (NWEKA(B. (NhRESTOMATIQ(B. 10 (NKLASS(B. (NhRESTOMWATI DLQ OB]EOBRAZOWATELNYH U^REVDENIJs (Nw DWUH ^ASTQH(B. (N~AST (BIs - (Nw(B. (Na(B. (N~ALMAEW(B.s; (Ns(B. (Na(B. (NzININs ((NmOSKWAs (NrUSSKOE SLOWOs, 2006)
(Nw U^EBNOJ HRESTOMATII SOSTAWLENNOJ W SOOTWETSTWII S SODERVENNEM gOSUDARSWENNOGO OBRAZOWATELXNOGO STANDARTAs
Keywords: (NlITERATURAs